Impact of Maintenance Practices on Plant Service Quality - Godse, Nitin; Henry, D. (SFIMAR Research Review, 2021)
Today's world is highly competitive, like never before. New technologies, machines, human beings are getting increasingly productive to sustain and survive in the world. In today’s globalized world, India’s position as a manufacturing force is getting noticed. Hence, the scale of efficiency has become global benchmark. Maintenance of engineering equipment and machines has become a challenge due to size, cost, complexity and competition. Although progress has been made in maintaining equipment in reasonable manner, there is a definite need for effective asset management and maintenance practices that will positively influence critical success factors such as safety, product quality, speed of innovation, price, profitability, technical obsolesce, and reliable delivery. In competitive world there is a need to reduce manufacturing cost. Also, there is humungous pressure on manufacturing function to adopt new technologies methods to improve productivity. One of the ways to gain competitive advantage is to pursue lean manufacturing. There are only a few companies addressing the significant synergies of various management practices and maintenance excellence. Many industries do not understand or not aware of one big opportunity area. The huge opportunity to reduce the manufacturing cost especially, in a plant where there is a capacity crunch is not appreciated by all. ‘Management practices’ is not just a buzz word but is a reality today and these practices can bring about huge savings in manufacturing costs. In industrial world the awareness of these important practices is rapidly increasing. However, the effectiveness and result orientation towards these activities varies a lot. Hence, this has become a topic of research and efforts are made to understand the practices, factors, actions and their impact and results. Objectives like achieving zero breakdowns, enhancing life of critical assets, analysing the breakdowns using appropriate tools and reducing the cost of maintenance is a science now. The science of maintenance is ever developing, and it is important to know the latest developments in the field of maintenance in order to sustain the results.